Apriori Algorithm for the Data Mining of Global Cyberspace Security Issues for Human Participatory Based on Association Rules - Li, Zhi; Li, Xuyu; Tang, Runhua; Zhang, Lin (Frontiers in Psychology, 2021)
The work studied global cyberspace security issues, breaking the stereotype of people's cognition of cyberspace problems, and reflecting the relationship between interdependence and association. Based on the Apriori algorithm in association rules, 181 strong rules were mined from 30 target websites and 56,096 web pages associated with global cyberspace security. Moreover, the work analyzed support, confidence, promotion, leverage, and reliability to achieve comprehensive coverage of data. 15,661 sites mentioned cyberspace security-related words, from the total sample of 22,493 professional websites, accounting for 69.6%. While only 735 sites mentioned cyberspace security-related words, from the total sample of 33,603 non-professional sites, accounting for 2%. Restricted by language, the number of samples of target professional websites and non-target websites was limited. Meanwhile, the number of selection of strong rules is not perfect. Nowadays, the cores of global cyberspace security issues are internet sovereignty, cyberspace security, network attack, cybercrime, data leakage, and data protection.